2023
DOI: 10.3390/membranes13010102
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Antibiotic-Releasing Polymer: Physicochemical Characterization and Drug Release Patterns

Abstract: Conventional drug delivery has its share of shortcomings, especially its rapid drug release with a relatively short duration of therapeutic drug concentrations, even in topical applications. Prolonged drug release can be effectively achieved by modifying the carrier in a drug delivery system. Among the several candidates for carriers studied over the years, poly (ether ether ketone), a biocompatible thermoplastic, was chosen as a suitable carrier. Its inherent hydrophobicity was overcome by controlled sulfonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The sulfonated polymers, with a high degree of sulfonation, can swell or form emulsion and were found to be difficult to isolate [42]. In the reported literature, the SPEEK polymer showed degradation and elevated hydrophilicity as the sulfonation increased which is similar to the current investigation [43,44]. The polymer PEK's insolubility and high melting temperatures impose processing and polymerization constraints [40]; due to this behavior, the PEK has a lower rate of sulfonation than the PEEK.…”
Section: Sulfonationsupporting
confidence: 82%
“…The sulfonated polymers, with a high degree of sulfonation, can swell or form emulsion and were found to be difficult to isolate [42]. In the reported literature, the SPEEK polymer showed degradation and elevated hydrophilicity as the sulfonation increased which is similar to the current investigation [43,44]. The polymer PEK's insolubility and high melting temperatures impose processing and polymerization constraints [40]; due to this behavior, the PEK has a lower rate of sulfonation than the PEEK.…”
Section: Sulfonationsupporting
confidence: 82%
“…The drug release rate can be determined by measuring the amount of drug released over time [ 108 ]. This can be effected by using various analytical techniques, such as UV-Vis spectroscopy, high-performance liquid chromatography (HPLC), or mass spectrometry.…”
Section: Intrinsically Disordered Synthetic Polymersmentioning
confidence: 99%
“…This type of mechanism typically indicates a release behavior that deviates significantly from Fickian diffusion, where the drug-release rate is not solely dependent on the concentration gradient but may involve additional factors like erosion, swelling, or relaxation of the matrix material. Regardless of the solubility of the antibiotic, the release of drugs from the hydrogel was most likely regulated via a diffusion mechanism [48,49]. Fick diffusion suggested that the hydrogel network was relaxed after the dissolution medium penetrated the hydrogel matrix.…”
Section: Kinetic Modelmentioning
confidence: 99%